2016
DOI: 10.1155/2016/4842814
|View full text |Cite
|
Sign up to set email alerts
|

Parents Support Implementation of HIV Testing and Counseling at School: Cross-Sectional Study with Parents of Adolescent Attending High School in Gauteng and North West Provinces, South Africa

Abstract: Background. A formative assessment of the implementation of HIV testing and counseling (HTC) at school showed high acceptability and willingness to test among learners. However, the success of the proposed HTC depends on the support and acceptability of key stakeholders, including the parents. The aim of the study was to assess the opinions and acceptability of the implementation of HTC at school among parents of adolescents in high school. Methods. This was a cross-sectional household survey conducted with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…To increase the uptake of HIV Testing, several models suiting individual and provider's needs such as HIV testing and counseling (HTC), provider-initiated testing and counseling (PITC), home-based HIV counseling and testing (HBCT) and HIV self-testing, have been adopted overtime. 1 HIV testing and counseling is the most common mode globally 1 and plays a link between prevention and mitigating activities. For those who are still HIV negative, HTC can be an incentive to change highrisk sexual behavior; while for those who are already positive, it can serve as a link to care, support and treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the uptake of HIV Testing, several models suiting individual and provider's needs such as HIV testing and counseling (HTC), provider-initiated testing and counseling (PITC), home-based HIV counseling and testing (HBCT) and HIV self-testing, have been adopted overtime. 1 HIV testing and counseling is the most common mode globally 1 and plays a link between prevention and mitigating activities. For those who are still HIV negative, HTC can be an incentive to change highrisk sexual behavior; while for those who are already positive, it can serve as a link to care, support and treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary findings were reported in Zungu et al's survey conducted in SA in 2016; where majority of participants aged 15 years and older perceived they were at high risk to HIV infection [27]. The majority of research that has investigated risk perception to HIV infection used quantitative approaches [3,7,[23][24][25][26][27]. Although previous research showed similarities in perceptions of low risk to HIV infection, our study was different in that we used a qualitative approach and focused on youth aged 15-24 years, an age group identified as high risk for HIV infection [12].…”
Section: Discussionmentioning
confidence: 98%
“…It also seemed that youth were unaware that their risk would be high even when in stable partnerships [ 3 ]. Surveys conducted in other populations found that majority of participants reported low risk perceptions to HIV infection despite having engaged in high risk sexual behaviours [ 3 , 23 25 ]. In other African countries, such as Zimbabwe and Ghana, similar findings were described where youth perceived their risk to HIV infection as low despite being exposed to high risk sexual behaviours [ 7 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach might be to provide large-scale school-based HTC. In a survey in South Africa, over 90% of parents supported HIV testing at schools [31].…”
Section: Discussionmentioning
confidence: 99%